![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
7A=7^2+7^3+7^4+....+7^100
A=7+7^2+7^3+....+7^99
6A=7^100-7
khi đó ta có
![](https://rs.olm.vn/images/avt/0.png?1311)
a;2 mu x =2 mu 6 .Vậy x=6
- b,7 mu x=49
- 7mu x -1x=7 mu 2
- 7mu x=2-1
- x=1
- c,(x+1)mu 5=2 mu 5
- x+1=2
- x=2+1
- x=3
![](https://rs.olm.vn/images/avt/0.png?1311)
Nguyễn Khánh Phương
Bài 1 :
a) 149 - ( 35 : x + 3 ) x 17 = 13
( 35 : x + 3 ) x 17 = 149 - 13
( 35 : x + 3 ) x 17 = 136
( 35 : x + 3 ) = 136 : 17
( 35 : x + 3 ) = 8
35 - x = 8 - 3
35 - x = 5
x = 35 - 5
x = 30
b, 121 : 11 − ( 4x + 5 ) : 3 = 4
11 − 4x + 5 : 3 = 4
4x + 5 : 3 = 11 − 4
4x + 5 : 3 = 7
4x + 5 = 7 x 3
4x + 5 = 21
4x = 21 − 5
4x = 16
x = 16 : 4
x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^2+5\right)\left(x^2-49\right)=0\)
\(\left(x^2-49\right)=0\) vì \(x^2+5>0\)
\(\Rightarrow x^2=49\)
\(\Rightarrow x=\pm7\)
vậy \(x=\pm7\)
\(\left(x^2+5\right)\left(x^2-7\right)< 0\)
\(\left(x^2-7\right)< 0\)
\(\left(x-\sqrt{7}\right)\left(x+\sqrt{7}\right)< 0\)
\(\hept{\begin{cases}x-\sqrt{7}>0\\x+\sqrt{7}< 0\end{cases}}\) hoặc \(\hept{\begin{cases}x-\sqrt{7}< 0\\x+\sqrt{7}>0\end{cases}}\)
\(\hept{\begin{cases}x>\sqrt{7}\\x< -\sqrt{7}\end{cases}}\) hoặc \(\hept{\begin{cases}x< \sqrt{7}\\x>-\sqrt{7}\end{cases}}\)
đến đây tự làm tiếp
\(\left(x^2+5\right)\times\left(x^2-49\right)=0\)
Vậy \(\orbr{\begin{cases}x^2+5=0\\x^2-49=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2=-5\\x^2=49\end{cases}}\)
Mà \(x^2\ge0\Rightarrow x^2=-5\)(loại)
Vậy \(x^2=49\)
Nên \(\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(7^x\times49=7^{32}\)
\(\Rightarrow7^x\times7^2=7^{32}\)
\(\Rightarrow7^{x+2}=7^{32}\)
\(\Rightarrow x=30\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-4\right)^9=49.\left(x-4\right)^7\\ =>\left(x-4\right)^9:\left(x-4\right)^7=49\\ =>\left(x-4\right)^2=49\\ =>\left[{}\begin{matrix}x-4=7\\x-4=-7\end{matrix}\right.\\ =>\left[{}\begin{matrix}x=11\\x=-3\end{matrix}\right.\)
(x - 4)9 = 49 . (x - 4)7
(x - 4)9 : (x - 4)7 = 49
(x - 4)2 = 72 = (-7)2
TH1 : TH2 :
(x - 4)2 = 72 (x - 4)2 = (-7)2
x - 4 = 7 x - 4 = -7
x = 7 + 4 x = -7 + 4
x = 11 x = -3
Vậy x = 11 Vậy x = -3
=>4x+2=2x+2
=>2x=0
=>x=0
\(7^{4x}+2=49^x+1\)
\(\Leftrightarrow4x+2=2\left(x+1\right)\)
\(\Leftrightarrow4x+2=2x+2\)
\(\Leftrightarrow4x-2x=2-2\)
\(\Leftrightarrow2x=0\)
\(\Leftrightarrow x=0\)